2020
DOI: 10.1186/s13014-020-01548-w
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated palliative volumetric modulated arc radiotherapy with the Radiation Oncology Study Group 8502 “QUAD shot” regimen for incurable head and neck cancer

Abstract: Background: To review a single institutional experience of the Radiation Therapy Oncology Group (RTOG) 8502 "QUAD shot" regimen using volumetric modulated arc radiotherapy (VMAT) for incurable head and neck cancer (HNC). Methods: Thirty-four consecutive patients with HNC were treated with at least one cycle of the RTOG 8502 regimen. Treatment plans included the use of VMAT with 6 MV photons generated by a linear accelerator. Two daily fractions of 3.7 Gy were delivered with an interval of at least 6 h for 2 co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…Tumor response was achieved in 85% of patients with symptom relief in 77% of the cases, the delivery of at least 2 treatment sessions being associated with a favorable response, and a median OS of 5.7 months. The absence of acute or late grade ≥3 toxicities recommends this protocol, confirming the data obtained by Corry and collaborators in a phase II trial [ 1 , 2 , 3 , 4 , 5 , 13 , 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Radiotherapy For Hnc In the Immunotherapy Era—isittime Fosupporting
confidence: 83%
“…Tumor response was achieved in 85% of patients with symptom relief in 77% of the cases, the delivery of at least 2 treatment sessions being associated with a favorable response, and a median OS of 5.7 months. The absence of acute or late grade ≥3 toxicities recommends this protocol, confirming the data obtained by Corry and collaborators in a phase II trial [ 1 , 2 , 3 , 4 , 5 , 13 , 31 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Radiotherapy For Hnc In the Immunotherapy Era—isittime Fosupporting
confidence: 83%
“…Out of these, 40 were excluded, as they did not directly target H&N cancer, elderly patients, or HFRT. The remaining 17 papers were lastly included in this review (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Resultsmentioning
confidence: 99%
“…Median progression-free survival (PFS) was 4.4 months, and better PFS outcomes were observed only at the completion of both courses. No G3 toxicity was registered ( 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that hypofractionation and shortening total treatment time and potentially dose are satisfactory in a palliative situation to relieve patients of malignancy-associated burden. Still, the main objective of these studies was for rapid symptomatic improvement rather than local control [ 107 , 108 , 109 , 110 , 111 , 112 , 113 ].…”
Section: Current Trends In Managementmentioning
confidence: 99%